LCSR Workshop: Generative conversations to deepen our understanding of Resilience in Livestock Systems - Dohrn, S. (International Livestock Research Institute, 2022)
Report: Livestock, Climate and System Resilience workshop on generative conversations to deepen the understanding of Resilience in Livestock Systems on 7 & 8 September 2022 in Rome, Italy